2022
DOI: 10.1002/jhbp.1248
|View full text |Cite
|
Sign up to set email alerts
|

Bridging therapies for patients with hepatocellular carcinoma awaiting liver transplantation: A systematic review and meta‐analysis on intention‐to‐treat outcomes

Abstract: Introduction:Locoregional therapies are commonly used as bridging strategies to decrease the drop-out of patients with hepatocellular carcinoma (HCC) awaiting liver transplantation (LT). The present paper aims to assess the outcomes of bridging therapies in patients with HCC considered for LT according to an intention-to-treat (ITT) survival analysis. Material and methods: Medline and Web of Science databases were searched for reports published before May 2021. Papers assessing adult patients with HCC consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(111 reference statements)
1
9
0
Order By: Relevance
“…Locoregional therapy has been offered to waitlisted patients to avoid dropout ( 5 - 7 , 13 ) . Nevertheless, there is no consensus regarding this approach in the literature, mainly because of the difficulty of performing randomized, controlled prospective studies ( 5 , 12 , 21 , 22 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Locoregional therapy has been offered to waitlisted patients to avoid dropout ( 5 - 7 , 13 ) . Nevertheless, there is no consensus regarding this approach in the literature, mainly because of the difficulty of performing randomized, controlled prospective studies ( 5 , 12 , 21 , 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, their analysis included patients with tumors that had been downstaged. The most recent systematic review and meta-analysis on the topic in question ( 12 ) , using the concept of intention-to-treat in an original way, concluded that patients undergoing bridging therapy before liver transplantation, despite being on the waiting list for longer than those who did not undergo the procedure, had better post-transplant survival. Nevertheless, when the intention-to-treat analysis was performed, there was no difference between those two groups in terms of the one-, three-, or five-year survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they found no difference in successful downstaging between treatment modalities, but did note higher rates of tumor necrosis with Y-90. Tumor size and AFP stability/decrease over a period of 6 months has previously been shown to predict good outcomes post-LT [23,24]. Complete pathologic response to LRT is also a predictor of good outcomes [25].…”
Section: Downstaging To Transplantmentioning
confidence: 97%
“…Although their use is still controversial, locoregional treatment techniques such as percutaneous thermal ablation (by radiofrequency or microwave) and transarterial chemoembolization (TACE) are now in the toolbox of the interventional radiologist, being routinely applied at transplant centers to cure or inhibit the growth of HCC. This strategy, known as bridging therapy, is indicated when the time on the waiting list exceeds six months, and its use can avoid acquired ineligibility, thus improving LT efficacy and excluding patients with neoplasia that is more aggressive ( 6 ) .…”
mentioning
confidence: 99%